COMBINATION OF COMPUTED TOMOGRAPHIC IMAGING CHARACTERISTICS OF MEDIAL RETROPHARYNGEAL LYMPH NODES AND NASAL PASSAGES AIDS DISCRIMINATION BETWEEN RHINITIS AND NEOPLASIA IN CATS. Issue 6 (20th July 2015) - Nemanic, Sarah; Hollars, Katelyn; Nelson, Nathan C.; Bobe, Gerd
Abstract : Feline nasal diseases are a diagnostic challenge. The objective of this retrospective, cross‐sectional study was to determine whether computed tomography (CT) imaging characteristics of the medial retropharyngeal lymph nodes (MRPLN), alone or in combination with CT imaging characteristics of the nasal passages, could aid in differentiation between rhinitis and nasal neoplasia. Cats were recruited from record archives at two veterinary facilities during the period of 2008–2012. Selection criteria were presentation for chronic nasal discharge, contrast‐enhanced CT of the head that included the MRPLN, and rhinoscopic nasal biopsy resulting in diagnosis of rhinitis or neoplasia. For each CT scan, two board‐certified veterinary radiologists recorded MRPLN size, attenuation, heterogeneity, contrast‐medium enhancement, margination, shape, presence of a lymph node hilus, perinodal fat, turbinate lysis, paranasal bone lysis, and nasal mass. Both readers were unaware of patient information at the time of CT interpretation. Thirty‐four cats with rhinitis and 22 cats with neoplasia were included. Computed tomographic characteristics significantly associated with neoplasia included abnormal MRPLN hilus (OR 5.1), paranasal bone lysis (OR 5.6), turbinate lysis (5.6), mass (OR 26.1), MRPLN height asymmetry (OR 4.5), and decreased MRPLN precontrast heterogeneity (OR 7.0). The combined features predictive of neoplasia were a nasal mass with abnormal hilus (OR 47.7); lysis of turbinates/paranasal bones with abnormal MRPLN hilus (OR 16.2). Findings supported the hypothesis that combining CT features of the nasal passages and MRPLN aided in differentiating rhinitis from neoplasia in cats.